Estimating the annual economic burden for the management of patients with transthyretin amyloid polyneuropathy in Spain. (3rd September 2021) - Galan, Lucia; Gonzalez-Moreno, Juan; Martínez-Sesmero, José Manuel; Muñoz-Beamud, Francisco; Santos-Rubio, Maria Dolores; Tran, Diana; Lebeau, Paul; Stewart, Michelle; Mallaina, Pablo; Tarilonte, Patricia; Peral, Carmen; Rozenbaum, Mark H
ABSTRACT: Background : Transthyretin amyloid polyneuropathy (ATTR-PN) is a fatal disease associated with substantial burden of illness. Three therapies are approved by the European Medicines Agency for the management of this rare disease. The aim of this study was to compare the total annual treatment specific cost per-patient associated with ATTR-PN in Spain. Methods : An Excel-based patient burden and cost estimator tool was developed to itemize direct and indirect costs related to treatment with inotersen, patisiran, and tafamidis in the context of ATTR-PN. The product labels and feedback from five Spanish ATTR-PN experts were used to inform resource use and cost inputs. Results : Marked differences in costs were observed between the three therapies. The need for patisiran- and inotersen-treated patients to visit hospitals for pre-treatment, administration, and monitoring was associated with increased patient burden and costs compared to those treated with tafamidis. Drug acquisition costs per-patient per-year were 291, 076€ (inotersen), 427, 250€ (patisiran) and 129, 737€ (tafamidis) and accounted for the majority of total costs. Overall, the total annual per-patient costs were lowest for patients treated with tafamidis (137, 954€), followed by inotersen (308, 358€), and patisiran (458, 771€). Conclusions : Treating patients with tafamidis leads to substantially lower costs and patient burden than with inotersen or patisiran.